Dietary resistant starch ameliorating lipopolysaccharide-induced inflammation in meat ducks associated with the alteration in gut microbiome and glucagon-like peptide 1 signaling - Simeng Qin; Weiqiang Bai; Todd J. Applegate; Keying Zhang; Gang Tian; Xuemei Ding; Shiping Bai; Jianping Wang; Li Lv; Huanwei Peng; Yue Xuan; Quifeng Zeng (Journal of Animal Science and Biotechnology, 2022)
Abstract Background Consumption of resistant starch (RS) has been associated with various intestinal and systemic health benefits, but knowledge of its effects on intestinal health and inflammatory response in stressed birds is limited. Here, we examined how dietary RS supplementation from 12% raw potato starch (RPS) modulated inflammatory severity induced by lipopolysaccharide (LPS) in meat ducks. Results LPS administration at 14, 16, and 18 d (chronic challenge) decreased body weight (BW) and glucagon-like peptide 1 receptor (GLP-1R) level with higher intestinal permeability and inflammation, evident by higher pro-inflammatory cytokine levels. Dietary 12% RPS supplementation enhanced Claudin-1 and GLP-1R expression, along with lower levels of inflammatory factors in both ileum and serum. Microbiome analysis showed that RS treatment shifted microbial structure reflected by enriched the proportion of Firmicutes, Bifidobacterium, Ruminococcus, etc. Dietary RS addition also significantly increased the concentrations of propionate and butyrate during chronic LPS challenge. Furthermore, response to acute challenge, the ducks received 2 mg/kg BW LPS at 14 d had higher concentrations of serum endotoxins and inflammatory cytokines, as well as upregulated transcription of toll like receptor 4 (TLR4) in ileum when compared to control birds. Analogous to GLP-1 agonist liraglutide, dietary RS addition decreased endotoxins and inflammation cytokines, whereas it upregulated the GLP-1 synthesis related genes expression. Meanwhile, dietary RS supplementation suppressed the acute LPS challenge-induced TLR4 transcription. Conclusions These data suggest that dietary 12% RPS supplementation could attenuate the LPS-induced inflammation as well as intestinal injury of meat ducks, which might involve in the alteration in gut microbiota, SCFAs production and the signaling pathways of TLR4 and GLP-1/GLP-1R.